Risk factors for syphilis in young women attending a family health program in Vitória, Brazil Fatores de risco para sífilis, em mulheres jovens, atendidas pelo programa de saúde da família em Vitória (ES), Brasil - Angélica Espinosa Miranda; Nínive Camilo Figueiredo; Valdir Monteiro Pinto; Kimberly Page; Sinésio Talhari (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: The high prevalence of STDs among women indicates the need to implement approaching techniques, case detection and prevention of new cases. OBJECTIVES: To describe the frequency of risk factors for syphilis and assess attitudes towards sexual risk in a population of young women in Vitória, ES. METHODS: Cross-sectional, population-based study, performed in Vitória. Interviews were held and VDRL and MHA-TP were investigated in blood samples. RESULTS: Among the 904 eligible women (18-29 years) sampled from the Family Health Program (FHP), 11 were diagnosed with syphilis, a prevalence of 1.2% (CI95% 0.5-1.9). Median age was 23 years (interquartile range 20-26 years); 65.7% of participants were in high school or college and 85.4% lived with their family or sexual partner. Factors associated with syphilis included: lower educational level (<8 years of schooling) [Adjusted Odds Ratio aOR=4.3 (CI 95% 1.01-17.99)]; >1 lifetime sexual partners [(aOR) =6.50 (CI95% 1.37-30.82)], and history of a previously diagnosed STD [aOR=10.3 (CI95% 2.37-44.33)]. Two thirds (67.7%) of the women surveyed agreed that it is not easy to tell their sexual partner they do not want to have sex without condoms; 52.3% thought it is difficult to use condoms in all sexual intercourses, and 36.2% said they cannot do anything if their partner refuses to use condoms. CONCLUSIONS: Using the FHP as an approach to perform routine VDRL can contribute to decreasing the vulnerability of these women and help control congenital syphilis. FUNDAMENTOS: A prevalência elevada de DST entre as mulheres indica a necessidade de implementação de abordagem, de detecção de casos e de prevenção de novos agravos. OBJETIVO: descrever a frequência dos fatores de risco para sífilis e as percepções de risco sexual, em mulheres jovens, na cidade de Vitória, ES. MÉTODOS: Estudo populacional, em corte-transversal, por amostragem, realizado em Vitória. Foram realizadas entrevista e pesquisa de VDRL e MHA-TP em amostra de sangue. RESULTADOS: Entre as 904 mulheres elegíveis (18-29 anos) selecionadas pelo Programa de Saúde da Família (PSF), 11 foram diagnosticadas com sífilis sendo a prevalência de 1,2% (IC95% 0,5-1,9). A mediana de idade foi de 23 anos (distância interquartil de 20-26 anos); 65,7% das participantes alcançavam o ensino médio ou superior e 85,4% moravam com a família ou com o parceiro sexual. Fatores associados com a sífilis: menor nível educacional (<=oito anos de estudo) [Odds ratio ajustado (Ora) =4,3 (IC95% 1,01-17,99)]; ter tido mais de um parceiro na vida [ORa=6,50 (IC95% 1,37-30,82)] e história prévia de DST [ORa=10,3 (IC95% 2,37-44,33)]. Dois terços (67,7%) das mulheres entrevistadas relataram não achar fácil dizer ao parceiro que não fará sexo sem preservativo, 52,3% consideram difícil usar preservativo em todos os intercursos sexuais e 36,2% acham que não há o que fazer, se o parceiro recusar usar preservativo. CONCLUSÕES: A utilização do PSF como porta de entrada para a realização do VDRL, na rotina de atendimento, pode contribuir para diminuir a vulnerabilidade destas mulheres e ajudar no controle da sífilis congênita.